Depenalisasi Sebagai Kebijakan Hukum Pidana Terhadap Pecandu Narkotika - I Gede Agus Purna Jaya; I Nyoman Putu Budiartha; Anak Agung Sagung Laksmi Dewi (Jurnal Analogi Hukum, 2019)
Apart from depenalization, actually the legal product for drug users in Indonesia has been published since 1971, in the form of a Presidential Instruction that still combines the prevention of narcotics hazards with other matters considered threatening state security. Up to several times the issuance of legal products, in the end Law No. was born. Concerning Narcotics UU no. 35 of 2009 concerning Narcotics is the addition of violence from the two previous Narcotics Laws. The formulation of the problem in this study is as follows: how is the regulation of depenization of narcotics addicts in positive criminal law at this time and how to regulate depenalization in the future for narcotics addicts. The type of research used in this study is normative legal research. The conclusions in this study are as follows: Criminal Code and Law No. 35 of 2009 concerning Narcotics as a positive law in Indonesia has not accommodated the depenalization of narcotics addicts explicitly, because there are several articles which are multi-interpreted. In Law No. 35 of 2009 concerning Narcotics ensnare narcotics addicts with criminal sanctions as determined in Articles 117 and 127 and actions in the form of mandatory rehabilitation specified in Article 54 of Law No. 35 of 2009. Where there will be a need to improve the RKUHP and Law No. 35 of 2009 by emphasizing the existence of provisions regarding depenalization of narcotics addicts. In conclusion, it can be accommodated in BOOK II CHAPTER XVII concerning criminal acts of Narcotics and Psychotropic abuse in the Criminal Procedure Code.